Dynamic Coding of Taste Stimuli in the Brainstem: Effects of Brief Pulses of Taste Stimuli on Subsequent Taste Responses - Di Lorenzo, Patricia M. (J Neurosci, 2003)
Recent studies have suggested that the response profiles of taste-responsive cells in the brainstem may be modulated by inhibitory interactions, potentially originating from activity in peripheral taste nerves. This idea was explored by testing the hypothesis that brief (100 msec) pulses of taste stimuli would alter the responses to subsequently presented tastants in the nucleus of the solitary tract (NTS) of urethane-anesthetized rats. Pulses of taste stimuli, called prepulses, were followed by a 3 sec presentation of the same or different taste stimulus. The prepulse-stimulus interval was either 1 or 5 sec, during which the tongue was rinsed with distilled water. Taste stimuli consisted of 0.1 m NaCl, 0.5 m sucrose, 0.01 m quinine HCl, and 0.01 m HCl. Taste prepulses suppressed (or enhanced) subsequent taste responses in 30 of 49 (61%) units when the prepulse-stimulus interval was 1 sec but were ineffective when this interval was 5 sec. Most commonly, NaCl or HCl prepulses attenuated the response to quinine. Control experiments showed that these effects were not attributable to adaptation, mixture effects, or response variability. In 19 (39%) of the units tested, effects of prepulses were large enough to change the order of effectiveness of the taste stimuli. Taste responses in these cells were “dynamically tuned” in that the magnitude of response was a function of the taste stimulus that immediately preceded it. Dynamic tuning may be the result of inhibitory interactions within the NTS; cells that show dynamic tuning may have a unique function in taste coding.